A Comprehensive Systematic Review of The Role of Screening Programs in Preventing Blindness in Primary Setting - Nathasya Pratiwi (International Medical Journal Corp. Ltd, 2025)
Introduction: Blindness and visual impairment represent significant global public health challenges, with many causes being preventable or treatable if detected early. Screening programs in primary care settings are widely advocated as a key strategy to reduce the burden of avoidable vision loss. However, the effectiveness of these programs varies substantially across different eye conditions, populations, and healthcare contexts. Methods: This comprehensive systematic review synthesises evidence from 80 studies examining the role of screening programs in preventing blindness within primary care settings. The review employed a structured screening process to include studies conducted in primary care, involving systematic screening interventions, with outcomes related to blindness prevention. Data extraction covered screening program details, primary care context, target population, visual outcomes, effectiveness results, implementation factors, and economic considerations. Results: The evidence reveals a paradox: while screening effectively identifies individuals with visual impairment, it does not consistently lead to improved visual outcomes at the population level. General visual acuity screening in older adults showed no significant benefit in improving vision or clinical outcomes (Clarke et al., 2018; Smeeth et al., 2003; Chou et al., 2016). In contrast, screening for diabetic retinopathy (DR) demonstrated efficacy, with telemedicine and AI-supported approaches significantly increasing screening uptake, detection rates, and referral adherence (Mansberger et al., 2015; Mathenge et al., 2022; Harding et al., 2023). Evidence for glaucoma population screening remains insufficient (Mangione et al., 2022), while preschool vision screening for amblyopia shows modest benefits (Schmucker et al., 2009). Newborn red reflex testing may improve early detection of congenital cataracts (Malik et al., 2022). Economic analyses indicate that telemedicine and AI-supported screening, particularly for DR, are cost-effective, especially in resource-limited settings (Avidor et al., 2020; Teo & Ting, 2023). Discussion: The disparity in outcomes underscores the critical influence of context, including baseline healthcare access, the natural history of the disease, availability of effective treatment, and the strength of referral pathways. Successful programs integrate technology with systemic support, such as patient navigation and removal of financial barriers. Conclusion: Screening is not a uniformly effective intervention for all eye conditions in all settings. Its value is highest for conditions like diabetic retinopathy within defined high-risk populations and in contexts with limited baseline eye care access. Future programs should be condition-specific, contextually tailored, and designed as integrated care pathways rather than isolated detection activities.